Macromol. Rapid Commun. 1/2018. Issue 1 (8th January 2018) - ter Schiphorst, Jeroen; Melpignano, Giuseppe G.; Amirabadi, Hossein Eslami; Houben, Menno H. J. M.; Bakker, Sterre; den Toonder, Jaap M. J.; Schenning, Albertus P. H. J.
Abstract : Back Cover : The cover image depicts a light‐responsive, passive micromixer in its swollen state, which mixes blue and yellow fluids using slanted groove structures. The molecule on the left is a protonated merocyanine, resulting in a swollen hydrogel, illustrated by the yellow disk. When illuminated, the spiropyran on the right is formed, resulting in a collapsed hydrogel, illustrated by the white disk. Further details can be found in article number 1700086 by Jaap M. J. den Toonder, * Albertus P. H. J. Schenning, * and co‐workers. The cover was designed by Mats Björklund.